Vasodilator-stimulated phosphoprotein-deficient mice demonstrate increased platelet activation but improved renal endothelial preservation and regeneration in passive nephrotoxic nephritis. - Hohenstein, Bernd; Kasperek, Laura; Kobelt, Dieter-Johannes; Daniel, Christoph; Gambaryan, Stepan; Renne, Thomas; Walter, Ulrich; Amann, Kerstin Ute; Hugo, Christian (Journal of the American Society of Nephrology, 2005)
Vasodilator-stimulated phosphoprotein (VASP), an actin cytoskeletal protein, is expressed in various cell types including renal cells. In vitro studies provide evidence for a role of VASP regarding platelet activation, cell adhesion, migration, and capillary formation. The in vivo role of VASP was investigated in experimental inflammatory renal disease. Kidneys of healthy VASP deficient (-/-) and wild-type (wt) mice were compared regarding morphology and functional parameters. Passive nephrotoxic nephritis was induced in 28 VASP -/- and 28 wt mice; kidneys were harvested; and tissues were analyzed by morphometric, immunohistochemical, and electron microscopic techniques on days 3, 7, 14, and 28. The time course of disease in VASP -/- mice differed substantially and biphasically from that in wt controls. Early on, VASP -/- mice demonstrated increased platelet influx associated with augmented glomerular and tubulointerstitial inflammation and sclerosis. Whereas renal disease continuously worsened up to day 28 in wt controls, renal disease in VASP -/- mice hardly progressed after day 3 as assessed by various injury indices. This long-term improvement of renal histology in VASP -/-compared with wt mice was associated with remarkable capillary preservation/regeneration up to day 28 mediated via an increased proliferative and a reduced apoptotic activity of VASP-negative peritubular endothelial cells. Despite an enhanced injury response early on, VASP -/- mice are protected from long-term progression of nephrotoxic nephritis, which is associated with improved renal endothelial cell preservation and regeneration. Copyright © 2005 by the American Society of Nephrology.
UnivIS-Import:2017-03-24:Pub.2005.med.MKIPIII.MKIPLA.vasodi